PROGNOSTIC FACTORS FOR TREATMENT OUTCOMES OF FLAT WARTS IN CHILDREN TREATED WITH TOPICAL 10% ZINC SULPHATE SOLUTION (Vietnam Journal of Community Medicine, 2026)
Objective: To compare treatment outcomes of pediatric flat warts using topical 10% zinc sulphate solution and 10% salicylic ointment, and to analyze clinical factors influencing treatment response for the two regimens.Methods: This study was conducted from September 2024 to July 2025 at the National Hospital of Dermatology and Venereology. Sixty-two patients with flat warts were randomly assigned to receive either topical 10% zinc sulphate solution or 10% salicylic ointment for four weeks. Treatment outcomes were evaluated based on the reduction in the number of lesions. Clinical factors analyzed included age, lesion distribution, lesion count, disease duration, and lesion location.Results: Topical 10% zinc sulphate demonstrated a higher good-response rate than 10% salicylic ointment across several clinical subgroups. In patients with scattered lesions, the good-response rate in the zinc sulphate group reached 64.9%, compared with only 10.0% in the salicylic group (p
Keywords: flat warts; children; zinc sulphate; salicylic; treatment response.